2006
DOI: 10.1523/jneurosci.3887-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal Set Activity Predicts Rule-Specific Neural Processing during Subsequent Cognitive Performance

Abstract: Prefrontal neurons have been shown to represent task rules. Here we show the mechanisms by which the rule-selective activity in the prefrontal cortex influences subsequent cognitive performance based on that rule. Using functional magnetic resonance imaging, we found that the frontopolar cortex interacted with posterior areas differently depending on whether subjects were going to perform a phonological or semantic task. Moreover, we found that the sustained "set" activity in this region predicted the activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

29
148
2
3

Year Published

2007
2007
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(182 citation statements)
references
References 37 publications
29
148
2
3
Order By: Relevance
“…These hypotheses are consistent with the previous literature on lateral PFC. In particular, there is a wealth of data suggesting that DL-PFC regions might be involved in the active maintenance of goals or task set information (4,16,17), and more recent work has also suggested that IFJ plays a critical role in cue-based encoding and updating of task sets in task switching and other cognitive control paradigms (18). Our findings extend this previous work by highlighting flexibility in the activation dynamics of these regions that has not been clearly demonstrated by previous work.…”
Section: Discussionsupporting
confidence: 79%
“…These hypotheses are consistent with the previous literature on lateral PFC. In particular, there is a wealth of data suggesting that DL-PFC regions might be involved in the active maintenance of goals or task set information (4,16,17), and more recent work has also suggested that IFJ plays a critical role in cue-based encoding and updating of task sets in task switching and other cognitive control paradigms (18). Our findings extend this previous work by highlighting flexibility in the activation dynamics of these regions that has not been clearly demonstrated by previous work.…”
Section: Discussionsupporting
confidence: 79%
“…Previous studies reported that the dorsolateral PFC participates in a range of processes related to executive behavioral control (32)(33)(34)(35). Among them, the role of the lateral PFC in response-guiding rules and strategies is of particular relevance to the present study.…”
Section: Discussionmentioning
confidence: 78%
“…1B, Left and SI Materials and Methods). Most importantly, this network included color-sensitive area V4 and motion-sensitive area hMT, as well as a number of frontal and parietal areas previously associated with task preparation and top-down attentional control (6,7,(30)(31)(32)(33). The preparatory network was used to derive 70 spherical, nonoverlapping network nodes (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…During goal-directed behavior, like the preparation of an upcoming task, relevant cortical regions are anticipatorily modulated (1)(2)(3)(4)(5), which has been shown to facilitate the detection and analysis of task-relevant stimuli (6)(7)(8)(9)(10)(11)(12)(13).…”
mentioning
confidence: 99%